Interpreting Self and Being Through the Metamorphoses of Muto - Burhanuddin, Azimuddin; Mohd Nor, Nurul Lina (Journal of Computing Technologies and Creative Content, 2020)
Muto is a short animation created by series of street art from around Buenos Aires, Argentina. Employing the techniques known as stop motion, the animation is showcasing ambiguous narrative through the sprouting sequences of bizarre characters and forms. Beginning with a white chalky drawn brick being pushed out from a wall, and a group of hands then escaping through the hole left by the brick, the narrative progresses with more depictions of distorted form of human figure move and metamorphosing persistently. This kind of animation is termed as abstract animation, where the content is usually conceptual and hard to be directly understand by its viewer. The imagery provided by abstract creation usually doesn’t call for a precise language of interpretation, but since it is grounded from the creator’s expression, certain interpretation may take place for the works to be completely reachable. In this essay, we will look closely into Muto, and will conduct an interpretive study on the animation. The outcome is hoped to feed the curiosity, contributing in animation studies, enhancing one appreciation on animation aesthetics and to deliver the meaning behind the film.